STUDIES ABOUT THE INSECT PESTS SUCCESSION ON TAMARIND,Tamarindus indica amarindus indica amarindus indica AT BASTAR DISTRICT OF AR DISTRICT OF CHHATTISGARH - AKHILESH KUMAR, A. K. GUPTA AND S. C. MUKHERJEE, (The Bioscan, 2018)
The experiment was conducted at Shaheed Gundadhoor College of Agriculture and Research Station, Jagdalpur, Bastar during 2015-16. In pest succession studies, six species of different insect pests were recorded, among these some were found damaging the tree while others were only visitors presented in very few numbers. Fruit borer, Cryptophlebia ombrodelta was categorized as major pest of tamarind. Its occurrence in the field was noticed throughout the green fruiting period. Maximum fruit borer infestation of 19.91 infested pods / unit area was recorded during second week of October with seasonal mean of 9.70 fruit borer infested pods / unit area. Peak population of mealy bugs was recorded during second week of October with 29.58 nymphs and adults / unit area .Two peaks of scale insects were observed, first in the fourth week of September followed by second week of November with 28.83 and 29.95 scale insects / unit area. Peak population of plant hopper 20.76 nymphs and adults / unit area recorded during second week of October. Peak activity period of tree hopper was recorded during second week of October with 5.73 nymphs and adults / unit area with the seasonal mean of 2.52 nymphs and adults / unit area.